Skilled Immigrants' Contribution to Productive Efficiency - Daehoon Nahm; Massimiliano Tani (Institute for the Study of Labor (IZA), 2014)
This paper studies whether skilled migrants contribute to the host country's 'productive efficiency' (Farrell, 1957) using input-output and immigration sectoral data for seven industries in twelve countries during the period 1999-2001. We find that skilled migrants contribute positively to a country's productive efficiency with the exception of the finance sector. The results broadly support the adoption of skill-biased migration policies.
Keywords: D24; F2; F66; J6; J24; 330; highly skilled migration; human capital; productive efficiency